Peningkatan Hasil Belajar PAI Siswa Kelas IV Menggunakan Metode Macke a Macth di UPTD SD Negeri 05 Makmur - Azizah, Elen (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
The learning outcomes in Islamic Education (PAI) at UPTD SD Negeri 05 Makmur remain very low due to students' lack of interest in learning and their easily distracted concentration during lessons. The objective of this classroom action research is to determine the learning outcomes of fourth-grade students in the PAI subject Asmaul Husna after using the Make a Match method at UPTD SD Negeri 05 Makmur. The research method employed was Classroom Action Research (CAR). The results showed that the application of the Make a Match method significantly improved students' learning outcomes. However, certain aspects, such as the duration of discussions and the variety of learning media, still need improvement. Based on these findings, the Make a Match method was deemed successful, and the research was concluded in the second cycle.